The child behavior checklist can aid in characterizing suspected comorbid psychopathology in clinically referred youth with ADHD. (June 2021) - Biederman, Joseph; DiSalvo, Maura; Vaudreuil, Carrie; Wozniak, Janet; Uchida, Mai; Woodworth, K. Yvonne; Green, Allison; Farrell, Abigail; Faraone, Stephen V.
Abstract: Objective: To examine the utility of the Child Behavior Checklist (CBCL) to aid in the identification of comorbid psychopathological conditions affecting referred youth with suspected ADHD prior to the evaluation. The CBCL is an easy-to-use assessment tool that may provide invaluable information regarding the severity and characteristics of the presenting complaints. Methods: The sample included 332 youths consecutively referred to an ADHD program for the assessment of suspected ADHD. Parents completed the CBCL, parent-rated ADHD Self-Report Scale (ASRS), Social Responsiveness Scale (SRS), and Behavior Rating Inventory of Executive Function (BRIEF). Because of the established association between the CBCL Attention Problems scale and a structured diagnostic interview of ADHD, all youths analyzed had abnormal Attention Problems T-scores (≥60). Results: Seventy-six percent of youths with elevated Attention Problems T-scores had ≥3 additional abnormal CBCL scales, suggesting they were likely affected with multiple comorbid psychopathological conditions. Moreover, 44% had ≥1 CBCL clinical scale with a T-score more severe than their Attention Problems T-score, suggesting the putative comorbid condition was more severe than the ADHD symptoms. Additional CBCL scale elevations were associated with more severe functional impairments as assessed by the ASRS, SRS, BRIEF, and CBCL competence scales. Conclusion: The CBCL obtained before the clinical assessment identified high rates of comorbid psychopathology in youths referred for the assessment of ADHD. It provided detailed information about the types and severity of suspected psychopathological conditions impacting a particular youth, which is critical to guide the assessing clinician on likely differing needs of the affected child.